Dialética da pratica e ação sem prática - Puppi, Ubaldo [UNESP] (Universidade Estadual Paulista (Unesp), Departamento de Filosofia, 1982)
O conceito de prática recobriria o de sistema de ação, não fosse a existência de sistemas de ação sem prática. Resta que uma prática é um sistema de ação. Como conseqüência, suposta a reciprocação de sistema com teoria e uma atenta inspeção nos termos da proposição, há equivalência semântica entre prática teóricae sistema de ação prático. Num e noutro caso, a contradição interna aos pares de conceitos se resolve dialeticamente. Graças à dialética, são fundidos numa unidade de sentido, síntese de tensões opostas. Daí a proposta de uma dialética da prática global, conjuntamente abstrata e histórica. Destotalizada ou à margem dessa dialética, pode ser destacada a ação sem prática, exemplificada no drama. Dramática é precisamente uma ação que não é prática. O tempo e o lugar da prática são a história e o mundo do homem; o tempo e o lugar do drama são a ficção cultural e a substância simbólica. Mimese da prática, o drama, reproduz, não os traços do modelo, mas a sua produção, tornando-se por sua vez modelo do modelo. Mimese não é cópia, é forma autônoma de eficiência, paradoxalmente sem prática mas especular.

The concept of practice would recover the concept of the system of action, if it were not for the existence of systems of action without practice. It remains that a practice is a system of action. As a consequence, supposing the reciprocality of the terms system and theory and a close inspection of the terms in the propositions, there is a semantic equivalence between theoretical practice and Practical system of action. In both cases, the contradiction between the pairs of concepts are resolved dialectically. Thanks to the dialectics, they are melted into one unit of meaning - a synthesis of opposing tensions. Hence, the proposal for a dialectics of global practice, at the same time abstract and historic. Detotalized or along the border of this dialectics, the action without practice as exemplified in the drama may be highlighted. Dramatic is precisely an action which is not practical. The time and the place of the practice are the history and the world of man; the time and the place of drama are the cultural fiction and the symbolic substance. As the mimesis of practice, the drama reproduces not the features of the model but its production and thus it becomes a model of the model. Mimesis is not copying; it is an autonomous form of efficiency, paradoxically without practice, but of course specular.
Dialectics of practice and action without practice
Keywords: Ação; prática; drama; mimese; sistema de ação; prática teórica; lógica; dialética; dialética da prática; salto dialético e processo dialético; Action; practice; drama; mimesis; system of action; theoretical practice; logic; dialectics; practice dialectics; dialectic jump and dialectic process